Charles Dickens : [a life defined by writing] - Slater, Michael (Yale University Press, 2009)
This long-awaited biography, twenty years after the last major account, uncovers Dickens the man through the profession in which he excelled. Drawing on a lifetime's study of this prodigiously brilliant figure, Michael Slater explores the personal and emotional life, the high-profile public activities, the relentless travel, the charitable works, the amateur theatricals and the astonishing productivity. But the core focus is Dickens' career as a writer and professional author, covering not only his big novels but also his phenomenal output of other writing--letters, journalism, shorter fiction, plays, verses, essays, writings for children, travel books, speeches, and scripts for his public readings, and the relationships among them. Slater's account, rooted in deep research but written with affection, clarity, and economy, illuminates the context of each of the great novels while locating the life of the author within the imagination that created them. It highlights Dickens' boundless energy, his passion for order and fascination with disorder, his organizational genius, his deep concern for the poor and outrage at indifference towards them, his susceptibility towards young women, his love of Christmas and fairy tales, and his hatred of tyranny.
Subtitle from cover.
Keywords: Dickens, Charles, -- 1812-1870.; Dickens, Charles, -- 1812-1870; Dickens, Charles.; Authors, English -- 19th century -- Biography.; Écrivains anglais -- 19e siècle -- Biographies.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Authors, English; 1800-1899; Biographies